2007
DOI: 10.1007/s10620-006-9705-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermented Soybean Meal on Intestinal Morphology and Digestive Enzyme Activities in Weaned Piglets

Abstract: The objective of the current experiment was to investigate the effect of Bacillus subtilis fermented soybean meal (FSBM) on intestinal morphology and digestive enzyme activities in piglets. Sixty crossbred (Duroc x Landrance x Yorkshire) piglets at an average weight of 8.62 kg were randomly allotted to two treatments and fed diets containing soybean meal (SBM) and FSBM, respectively. At the end of the experimental period, six piglets of each treatment were slaughtered humanly to collect the contents and tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 28 publications
8
78
1
2
Order By: Relevance
“…Feng et al (2007) quantified the enzymatic activity (in units of substrate composed per milligram of dry matter from digestion) in the duodenum, jejunum and ileum and verified an increase of 52 % in the proteolytic activity of trypsin in the duodenum and jejunum, with a decrease of this compound within the lumen. Furthermore, this activity increases the height of the villus and the depth of the crypt in the three segments of the large intestine, resulting in greater capacity of digestion and absorption.…”
Section: Performance Of Broiler Chickensmentioning
confidence: 90%
See 1 more Smart Citation
“…Feng et al (2007) quantified the enzymatic activity (in units of substrate composed per milligram of dry matter from digestion) in the duodenum, jejunum and ileum and verified an increase of 52 % in the proteolytic activity of trypsin in the duodenum and jejunum, with a decrease of this compound within the lumen. Furthermore, this activity increases the height of the villus and the depth of the crypt in the three segments of the large intestine, resulting in greater capacity of digestion and absorption.…”
Section: Performance Of Broiler Chickensmentioning
confidence: 90%
“…Another hypothesis refers to the presence of protease inhibitors in the composition of soybean meal that, as reported by Feng et al (2007), correspond to almost 3 mg g -1 of soybean dry matter. The use of processing to avoid such undesirable components is unavoidable.…”
Section: Performance Of Broiler Chickensmentioning
confidence: 93%
“…Many studies have reported the relationship between small-sized peptide ingestion and Ig concentration in blood. Wang et al (2003) demonstrated that adding 3 g of small peptides per kilogram BW to the basal diets of piglets increased the concentration of immunoglobulin, and Feng et al (2007) showed that fermented SBM having small-sized peptides increased the level of IgA and IgM, but not IgG, in broiler chickens. In chickens, IgG concentrations were greater in animals receiving mannan-oligosaccharide (MOS) compared with those of control animals (Savage et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Allergic factors cause hypersensitivity reactions, promoting a shortening of the intestinal villus and decreasing the ratio between the villi length and crypt depth (Thomaz et al, 2011). The presence of ANF in the diets of broilers from one to 21 days of age implies a reduction in feed intake, impaired digestion and utilization of nutrients (Feng et al, 2007;Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%